Performance of SPE electrodes in electrolytic regeneration process of desulfurization of iron complex. (19th April 2021) - Huang, Haiyan; Lv, Zeng; Shang, Jie; Yu, Ying; Chung, Keng H.
Abstract: In the alkaline system, the iron complex was used to absorb hydrogen sulfide to obtain sulfur, and the iron complex absorbent was oxidized and regenerated at the anode by electrolysis method for recycling, and hydrogen was obtained at the cathode. This process can recover both hydrogen and sulfur from hydrogen sulfide and avoid the harsh conditions of strong acidity. In this paper, SPE electrode is used in the oxidation and regeneration process of iron complex. The results show that the oxidation current density of iron complex at SPE electrodes are one order of magnitude higher than that of traditional electrodes, and the current efficiency is slightly lower than that of traditional electrode. The current efficiency of carbon cloth SPE electrode reaches 90% from 0.25 to 0.5V, the performance of complexed iron oxidation is better than that of the stainless-steel mesh SPE electrode, and the side reaction is mainly EDTA oxidation reaction. Highlights: We propose treatment H2 S using complexed iron as the electrochemical intermediate. We propose SPE electrodes for the oxidation process in the alkaline system. We discuss the performance of complexed iron oxidation of various electrodes.